Effect of Dust Accumulation on Performance of the Photovoltaic Panels in Different Climate Zones - Mohammadi, Fahimeh; Hajinezhad, Ahmad; Kasaeian, Alibakhsh; Moosavian, Seyed Farhan (International Journal of Sustainable Energy and Environmental Research, 2022)
With the increasing demand for energy globally and the need to reduce fossil fuels, paying attention to renewable and clean energy sources is necessary. Solar systems are viable among renewable energy sources for heat and electricity generation. In this study, an Off-grid solar system was investigated by considering the effect of climate conditions and environmental factors such as dust on the performance of PV panels. Performance and efficiency of PV system using PVsyst software in four cities of Iran (Mashhad, Abadan, Rasht, and Sanandaj) with different climates were presented. This study shows that most of the loss occurs in Sanandaj, with the cold and humid climate, which results show an 11.19% efficiency reduction. On the other hand, with its hot and humid climate, Abadan has an 8.33% loss due to the geographical location of this city in the vicinity of desert areas. With a temperate and humid climate, Rasht has a 2.27% decrease, and Mashhad, with a cold and dry climate, has a 2.19% decrease in yield.